REHABILITACJARehabilitation after cardiac surgery in the position paper from European Association for Cardiovascular Prevention and Rehabilitation: Secondary prevention through cardiac rehabilitation: from knowledge to implementation - Dylewicz, Piotr; Krzywicka-Michałowska, Monika (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
The positive results of rehabilitation and secondary prevention of patients after cardiac surgery are well documented. This is confirmed by the statements of the relevant scientific and political societies such as the European Heart Health Charter. In this paper we have tried to comment on the position of the Section of Cardiac Rehabilitation of the European Association for the Prevention and Cardiac Rehabilitation, which was published last year. The authors of the mentioned paper point out that preventive efforts are currently focused primarily on interventional cardiology and drug-medication therapy, both of which give short-term effects. Lifestyle modification, the necessary rehabilitation process and health education for each patient individually are necessary to obtain a long term and permanent improvement in health. This is obviously the main challenge of current medicine and it needs international efforts. Physical activity and diagnostic tests to obtain the individual training programme are considered as the main core components for the rehabilitation of cardiac patients. This is the first time that such a wide range of health issues and different programmes for patients after cardiac surgery, especially after heart transplantation, was noted. The criteria for stationary rehabilitation have been re-defined. In our opinion some questions need further discussion between wide medical associations experienced in those issues.